Faktor Perilaku Cuci Tangan Pakai Sabun (CTPS) di SMP - Bambang Murwanto (Politeknik Kesehatan Tanjung Karang, 2017)
Riskesdas (2013), Diarrhea is the number one cause of death in infants (31.4%), children under five (25.2). Whereas in all age groups is a cause number four, or 13.2%. Various factors affect the disease Diarrhoea among the factors of health behavior, especially the behavior of Handwashing with Soap that has been campaigned, both from the national level. As well as health offices District/City through PHC, especially in schools, including junior high school. The problem is to what extent the role of behavior Handwashing with Soap and the factors associated with it in school children. The purpose of this study was to determine the role of factors related to the behavior Handwashing with Soap, in junior high schools. This research method was quantitative observational with a cross sectional approach, with research time the months of April to July 2016. The study population was all students of SMP Negeri 1 Penengahan, South Lampung, 2016. Samples were taken by a proportional random sampling of 156 junior high school students. Subjects were children of class VII and Class VIII. The results of the study are of most variables are good (> 50%), except for the variable perception and the Role of Health who are poor (<50%), and the only variable values, Role of Teachers and the Role of Friends Schools that have a relationship significant overall Handwashing Behavior and Role of School Friend variable most dominant relationship.